Reducing neurodisparity: Recommendations of the 2017 AAN Diversity Leadership Program. (5th February 2019) - Marulanda-Londoño, Erika T.; Bell, Michelle W.; Hope, Omotola A.; Leacock, Rodney O.; O'Carroll, Cumara B.; Posas, Jose; Stover, Natividad P.; Young, Richard; Hamilton, Roy
Abstract : Many advances in prevention, diagnosis, and treatment of neurologic disease have emerged in the last few decades, resulting in reduced mortality and decreased disability. However, these advances have not benefitted all populations equally. A growing body of evidence indicates that barriers to care fall along racial and ethnic lines, with persons from minority groups frequently having lower rates of evaluation, diagnosis, and intervention, and consequently experiencing worse neurologic outcomes than their white counterparts. The American Academy of Neurology (AAN) challenged its 2017 Diversity Leadership Program cohort to determine what the AAN can do to improve quality of care for racially and ethnically diverse patients with neurologic disorders. Developing a fuller understanding of the effect of disparities in neurologic care (neurodisparity) on patients is an important prerequisite for creating meaningful change. Clear insight into how bias and trust affect the doctor–patient relationship is also crucial to grasp the complexity of this issue. We propose that the AAN take a vital step toward achieving equity in neurologic care by enhancing health literacy, patient education, and shared decision-making with a focus on internet and social media. Moreover, by further strengthening its focus on health disparities research and training, the AAN can continue to inform the field and aid in the development of current and future leaders who will address neurodisparity. Ultimately, the goal of tackling neurodisparity is perfectly aligned with the mission of the AAN: to promote the highest-quality patient-centered neurologic care and enhance member career satisfaction.